The prevalence of burnout in nurses working in private healthcare facilities in Mbombela/Nelspruit during the COVID-19 pandemic - Lourens, Dirk Cornelus (Stellenbosch : Stellenbosch University, 2022)
Thesis (MHumanRehabSt)--Stellenbosch University, 2022.